2022
DOI: 10.1002/aws2.1283
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging risk and data analytics for sustainable management of buried water infrastructure

Abstract: A proactive and sustainable asset management program is vital for utilities to maintain their capital assets at the required level of service, while ensuring that adequate funds are available for intervening when needed on their riskiest assets. One of the most popular methods for building such programs is by prioritizing capital investments based on the asset's risk of failure, which evaluates its likelihood or probability of failure and impact, or consequence of failure. This paper presents the application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For example, previous works have implemented analyses where every distribution main is ranked based on the future likelihood and consequence of failure, and asset management programs are designed to address the highest risk assets first (Chen, Riley, et al, 2020; Chen, Washington, et al, 2020). See other examples in Ganjidoost et al (2022), Vladeanu and Matthews (2019), Fontanazza et al (2015), and Puleo et al (2014) focusing on distribution mains, valves, and water meters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous works have implemented analyses where every distribution main is ranked based on the future likelihood and consequence of failure, and asset management programs are designed to address the highest risk assets first (Chen, Riley, et al, 2020; Chen, Washington, et al, 2020). See other examples in Ganjidoost et al (2022), Vladeanu and Matthews (2019), Fontanazza et al (2015), and Puleo et al (2014) focusing on distribution mains, valves, and water meters.…”
Section: Introductionmentioning
confidence: 99%
“…Ganjidoost et al (2018) developed three categories of infrastructure, socio‐political, and financial benchmarking performance indicators for water distribution and wastewater collection networks. They used SD to demonstrate how water utilities can utilize the proposed normalized and time‐integrated performance indicators to benchmark and compare their networks' short and long‐term performance against one another and their own strategic targets (Ganjidoost et al, 2018; Ganjidoost, Daly, & Baird, 2021; Ganjidoost, Knight, et al, 2021; Ganjidoost, Knight, et al, 2022; Ganjidoost, Vladeanu, & Daly, 2022a, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Katko et al (2010) suggested that the concept of integrating the management of water and wastewater infrastructure systems is familiar, but the idea as a whole has not been fully embraced. Many studies, including, but not limited to, Ganjidoost (2016), Ganjidoost et al (2017, 2018), Ganjidoost, Daly, and Baird (2021), Ganjidoost, Haas, et al (2015a, 2015b), Ganjidoost, Knight, et al (2021), Ganjidoost, Knight, et al (2022), Ganjidoost, Vladeanu, and Daly (2022a, 2022b), Ganjidoost, Younis, and Knight (2015), Mohammadifardi, Knight, and Unger (2019), Rehan et al (2011, 2013, 2015), Rehan, Knight, et al (2014), Rehan, Unger, et al (2014) along (Baah et al, 2015; Duchesne et al, 2013; Elsawah et al, 2016; Hawari et al, 2016; Kleiner et al, 1998a, 1998b; Mashford et al, 2010; Mazumder et al, 2021; Park et al, 2015; Roshani & Filion, 2013; Scheidegger et al, 2011; Scholten et al, 2014; Syachrani et al, 2011; Tran et al, 2010) have developed distinct and separate management models for water and wastewater infrastructure systems. The evaluation of these models indicates that the current management models and tools are applied to either water distribution or wastewater collection systems.…”
Section: Introductionmentioning
confidence: 99%